Pengembangan Sistem Angkutan Pelajar Perkotaan Berbasis Demand Angkutan Sekolah Kota Dumai (Studi Kasus : Kecamatan Sungai Sembilan Dan Medang Kampai - Kunia, Danu; Idham, Muhammad (Lembaga Teewan Journal Solutions, 2026)
The limited availability of school transportation services in Sungai Sembilan and Medang Kampai Districts, Dumai City, has resulted in most students relying on private vehicles for their daily trips to school. This study aims to analyze the demand for school transportation, determine service routes, develop an operational plan, and calculate the Vehicle Operating Costs (VOC) and school bus fares. The research employed a quantitative descriptive method through field surveys and travel demand analysis. The results indicate that the potential demand for school transportation reaches 1,928 students. Two service corridors were proposed, covering Sungai Sembilan and Medang Kampai Districts, with each corridor served by three buses. The operational schedule consists of 06:00–07:00 for morning school trips, 12:00–13:00 for elementary school student pick-up services, and 14:00–15:00 for junior high school student pick-up services. Based on the Vehicle Operating Cost (VOC) analysis, the fare charged to students is set at IDR 2,000 per passenger per trip under a partial subsidy scheme, with the remaining operating costs covered by the government. The proposed school transportation system is expected to support the implementation of a safer, more effective, and sustainable school transport service in Dumai City